E-Module Learning Media Ignition System Material Based on Flipbook: Media Pembelajaran E-Modul Materi Sistem Pengapian Berbasis Flipbook - Didiek Wahyu Wijayanto; Ibut Priono Leksono; Retno Danu Rusmawati (Wadah Inovasi Indonesia, 2022)
Background:The flipbook-based ignition system e-module is an electronic ignition system module that includes ignition system material whose material is equipped with pictures, video explanations of material and interactive quizzes that can be applied on line using a smartphone or computer without having to download it first. Methodology:This type of research is Research & Development (R&D) with the adaptation of the Dick and Carey model using data collection instruments in the form of questionnaires and expert reviews, while the data analysis technique uses qualitative descriptive analysis techniques and descriptive statistical analysis. Findings:The results showed the feasibility of the product with a percentage figure above 85% (very feasible). Conclusion:The developer concludes that the ignition system e-module development product based on flipbooks can be used as a learning medium in the subject of Light Vehicle Electrical Maintenance in class XI TKRO ignition system material, as evidenced by the results of questionnaires and comments from experts that are very good/appropriate with the percentage figures above. 85% Originality:This flipbook-based ignition system e-module development product has been validated by material experts, media experts, design experts, and colleagues who all meet the minimum educational criteria for a master's degree in their respective fields, and have gone through individual trials, small group trials, and revised field trials.